PENGARUH BERBAGAI CAMPURAN DAUN SINGKONG DAN ONGGOK TERFERMENTASI ASPERGILLUS NIGER TERHADAP KUALITAS BAHAN KERING, SERAT KASAR, DAN PROTEIN KASAR - Hendro Prastio; Liman Liman; Rudy Sutrisna; Muhtarudin Muhtarudin (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2022)
This study aimed to determine the effect of various mixture of cassava leaves and cassava waste fermented by Aspergillus niger on dry matter, crude fiber, and crude protein. This research was carried out in August 2021--September 2021 at the Animal Nutrition and Feeding Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The experimental design used was a completely randomized design (CRD) with 5 treatments and 3 replications. The treatments were cassava waste without mixture + Aspergillus niger 1% BK (P0), cassava leaves without mixture + Aspergillus niger 1% BK (P1), cassava waste 20% + cassava leaves 80% + Aspergillus niger 1% BK (P2), cassava waste 40% + cassava leaves 60% + Aspergillus niger 1% BK (P3), and cassava waste 60% + 40% cassava leaves + Aspergillus niger 1% BK (P4). The variables observed in this study included dry matter, crude fiber, and crude protein of product of fermentation. The data obtained were analyzed using analysis of variance with a significance level of 1% or 5% and continued with Duncan's Multiple Range Test. The results showed that fermentation with Aspergillus niger 1% BK could reduce the crude fiber content in a mixture of cassava waste and cassava leaves from 18.24% to 12.45% after fermentation, and could increase the crude protein content of fermented products. While the best response of fermentation of mixture of cassava waste and cassava leaves on the chemical quality of dry matter, crude fiber, and crude protein was obtained in a mixture of 40% cassava waste + 60% cassava leaves + Aspergillus niger 1% BK which produced 20.48% crude protein with low crude fiber of 10.81%. Keywords: Aspergillus niger, crude fiber, crude protein, Dry matter, fermentation